Intermittent theta burst stimulation to the left dorsolateral prefrontal cortex improves cognitive function in polydrug use disorder patients: a randomized controlled trial - Dong, Ling; Chen, Wen-Cai; Su, Hang; Wang, Mei-Ling; Du, Cong; Jiang, Xing-ren; Mei, Shu-fang; Chen, Si-Jing; Liu, Xiu-Jun; Liu, Xue-Bing (Frontiers in Psychiatry, 2023)
Background: Polydrug abuse is common among opioid users. Individuals who use both heroin and methamphetamine (MA) have been shown to experience a wide range of cognitive deficits. Previous research shows that repetitive transcranial magnetic stimulation (rTMS) can change cerebral cortical excitability and regulate neurotransmitter concentration, which could improve cognitive function in drug addiction. However, the stimulation time, location, and possible mechanisms of rTMS are uncertain. Methods: 56 patients with polydrug use disorder were randomized to receive 20 sessions of 10 Hz rTMS (n=19), iTBS (n=19), or sham iTBS (n=18) to the left DLPFC. All patients used MA and heroin concurrently. Cognitive function was assessed and several related proteins including EPI, GABA-Aα5, IL-10, etc. were quantified by ELISA before and after the treatment. Results: Baseline RBANS scores were lower than normal for age (77.25) (IQR 71.5-85.5). After 20 treatment sessions, in the iTBS group, the RBANS score increased by 11.95 (95% CI 0.02-13.90, p=0.05). In particular, there were improvements in memory and attention as well as social cognition. Following treatment, serum EPI and GABA-Aα5 were reduced and IL-10 was elevated. The improvement of immediate memory was negatively correlated with GABA-Aα5 (r=-0.646, p=0.017), and attention was positively correlated with IL-10 (r=0.610, p=0.027). In the 10 Hz rTMS group, the improvement of the RBANS total score (80.21±14.08 before vs.84.32±13.80 after) and immediate memory (74.53±16.65 before vs.77.53±17.78 after) was statistically significant compared with the baseline (p＜0.05). However, compared with the iTBS group, the improvement was small and the difference was statistically significant. There was no statistically significant change in the sham group (78.00±12.91 before vs.79.89±10.92 after) (p＞0.05). Conclusions: iTBS to the left DLPFC may improve cognitive function in polydrug use disorder patients. Its efficacy appears to be better than that of 10 Hz rTMS. The improvement of cognitive function may be related to GABA-Aα5 and IL-10. Our findings preliminarily demonstrate the clinical value of iTBS to the DLPFC to augment neurocognitive recovery in polydrug use disorders.